MacJannet School basketball team, 1938 (Tufts Archival Research Center, 2005)
2 x 2. Left to right, Beatrice Nimic, Nona Rider, Catherine Murphy, Kitty Reurs, Rosemary Murphy, Betty Hilgers, Barbara Spinning, and Margaret Ferber.